(untitled) (Olhar de Professor, 2024)
This article discusses the issue of privatizing education in Angola via the advancement of public policies that favor the private sector. The general objective of the study is to reflect on the guarantee of the right to compulsory basic education in the political scenario of the Angolan Educational System, in the face of privatization and financial dependence on international organizations. This research, with a quantitative-qualitative approach, was carried out using documentary-bibliographic methodology with the analysis of national legislation, plans and reports. The results of the study point to a growing trend towards the establishment of the private and public-private sector in the Angolan Educational System. The State of Angola needs to count on international financing from multilateral organizations to minimize weaknesses, which favors privatization. Private sector management weighs on the finances of parents and guardians.